Anxiety Experiences Among Pregnant Women During COVID-19 Pandemic - Metty Wuisang; Angelia Friska Tendean; Cherol Nelson Ering (NUTRIX, 2023)
Pregnant women are a group at risk of contracting COVID-19. This condition makes pregnant women often feel anxious about the possibility of exposure to COVID-19 infection. Anxiety that cannot be overcome will have a negative impact on the pregnant woman herself, such as preeclampsia and even miscarriage and the fetus, such as premature birth and low birth weight. This study aims to explore the anxiety experiences of pregnant women during the COVID-19 pandemic. This research was conducted in the North Minahasa area using a qualitative method with a phenomenological approach. Informants in this study amounted to 11 people. Methods of data collection using semi-structured video and face-to-face interviews. Anxiety experienced 4 themes that emerged, namely: 1) Anxiety about contracting, 2) Anxiety about other people's health, 3) Anxiety about doing antenatal care, and 4) Anxiety about childbirth. Health workers need to overcome anxiety in pregnant women so that negative impacts on pregnant women and the fetus can be avoided. Telehealth can be an alternative option to help pregnant women deal with anxiety during the COVID-19 pandemic. Keywords: Anxiety, COVID-19, Pregnant Women Abstrak Ibu hamil merupakan kelompok yang berisiko tertular COVID-19. Kondisi ini membuat ibu hamil kerap merasa cemas akan kemungkinan terpapar infeksi COVID-19. Kecemasan yang tidak bisa diatasi akan berdampak buruk pada ibu hamil itu sendiri seperti preeklampsia bahkan keguguran dan janin seperti lahir prematur dan berat badan bayi baru lahir rendah. Penelitian ini bertujuan untuk mengeksplorasi pengalaman kecemasan ibu hamil selama pandemi COVID-19. Penelitian ini dilakukan di daerah Minahasa Utara dengan menggunakan metode kualitatif dengan pendekatan fenomenologis. Informan dalam penelitian ini berjumlah 11 orang. Metode pengumpulan data menggunakan video semi terstruktur dan wawancara tatap muka. Kecemasan mengalami 4 tema yang muncul yaitu: 1) Kecemasan tertular, 2) Kecemasan terhadap kesehatan orang lain, 3) Kecemasan melakukan antenatal care, dan 4) Kecemasan terhadap persalinan. Tenaga kesehatan perlu mengatasi kecemasan pada ibu hamil sehingga dampak negatif pada ibu hamil maupun janin bisa terhindari. Telehealth dapat menjadi pilihan alternatif untuk membantu ibu hamil mengatasi kecemasan selama masa pandemi COVID-19. Kata Kunci: COVID-19, Ibu hamil, Kecemasan